1973
DOI: 10.1288/00005537-197306000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic granuloma of the temporal bone

Abstract: Three patients, all children, are presented with a diagnosis of eosinophilic granuloma isolated to the temporal bone. In two cases the disease was unilateral, and in the third, bilateral disease was encountered. General evaluations, audiometric studies, and laboratory findings will be discussed. X‐rays will be shown as well as photomicrographs of the gross and microscopic lesions to supplement this discussion. Our approach was surgical in all four ears involved. Radiation therapy was not utilized. A thorough r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
10

Year Published

1979
1979
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 15 publications
0
4
0
10
Order By: Relevance
“…Os temporale kann neben der Mastoidektomie über einen retroaurikulären Zugang die chirurgische Therapie als Radikaloperation, aber auch ausgeweitet als laterale Petrosektomie [7,15,28] erfolgen. In Tabelle 3 werden die intraoperativen Befunde der LCH des Felsenbeins zusammengefasst.…”
Section: Stellenwert Der Operativen Therapieunclassified
See 2 more Smart Citations
“…Os temporale kann neben der Mastoidektomie über einen retroaurikulären Zugang die chirurgische Therapie als Radikaloperation, aber auch ausgeweitet als laterale Petrosektomie [7,15,28] erfolgen. In Tabelle 3 werden die intraoperativen Befunde der LCH des Felsenbeins zusammengefasst.…”
Section: Stellenwert Der Operativen Therapieunclassified
“…Ein Befall einer Tonsille wurde langfristig nach Tonsillektomie kontrolliert [14]. Ein Polyp im Gehör-gang wurde lokal entfernt mit Küretta-ge der Basis vom angrenzenden Knochen [28]. Halslymphknoten werden regelmäßig im Rahmen auch systemischer Erkrankungen beschrieben und müssen im individuellen Fall differentialtherapeutischen Überlegungen unterzogen werden.…”
Section: Stellenwert Der Operativen Therapieunclassified
See 1 more Smart Citation
“…1 We report two cases of EG with bilateral damage to the temporal bones. In one, the initial symptoms and clinical course were ambiguous and rather unusual and constituted a difficult diagnostic problem.…”
mentioning
confidence: 93%
“…The patient was treated with chlorambucil, 3 mg/day, for two months, followed by cytostatic therapy with vincristine sulfate (Oncovin), 1 reported that of 50 patients seen by them, 34% were younger than the age of 4 and 74% were younger than the age of 20 years. There would appear to be a male predominance in EG.…”
mentioning
confidence: 99%